2016
DOI: 10.1001/jamaoncol.2015.5392
|View full text |Cite
|
Sign up to set email alerts
|

DPYDGenotyping to Predict Adverse Events Following Treatment With Fluorouracil-Based Adjuvant Chemotherapy in Patients With Stage III Colon Cancer

Abstract: eudract Identifier 2005-003463-23.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 27 publications
(21 reference statements)
6
58
1
Order By: Relevance
“…The objective of our case-control study was to analyse the two other variants, c.2846A>T and c.1679T>G, in subjects who have presented FAEs not DPYD*2A correlated, in order to confirm their clinical relevance and to evaluate their possible improvement of predicting toxicity when introduced in the pre-treatment screening. Furthermore, in consideration of the results of some recent studies, 5,[23][24][25] we evaluated the potential clinical impact of the c.2194G>A SNP, a more frequent variant of DPYD with an interesting correlation with fluoropyrimidine-related toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of our case-control study was to analyse the two other variants, c.2846A>T and c.1679T>G, in subjects who have presented FAEs not DPYD*2A correlated, in order to confirm their clinical relevance and to evaluate their possible improvement of predicting toxicity when introduced in the pre-treatment screening. Furthermore, in consideration of the results of some recent studies, 5,[23][24][25] we evaluated the potential clinical impact of the c.2194G>A SNP, a more frequent variant of DPYD with an interesting correlation with fluoropyrimidine-related toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…That study also confirmed the significant predictive value of rs67376798 (D949V), but not for DPYD *2A and DPYD *13, which are the other variants included in the Clinical Pharmacogenetics Implementation Consortium Guidelines. This apparently surprising discrepancy may simply be due to the low allelic variant frequency in the population studied by Boige et al [4]. Consequently, a strategy considering more frequent DPYD variants may be relevant to understand the cause-effect correlation between toxicity and heritability, which is currently lacking in the assessment of only rare variants.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Boige et al [4] made important advances in this direction by investigating 25 DPYD variants in a large cohort of patients with stage III colon cancer treated with FOLFOX4 adjuvant chemotherapy. Among the 12 DPYD variants found to be polymorphic, statistically significant associations with grade 3 or greater fluorouracil adverse events were observed for carriers of rs67376798 (D949V: OR 6.3; 95% CI 2.0-27.0) and rs1801160 (V732I: OR 1.7; 95% CI 1.3-2.4) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, genetic variants of DNA repair genes in the form of SNPs could modulate treatment response. A recent large pharmacogenetic analysis examining 66 SNPs showed that there is an association between SNPs in DNA repair genes and response to neoadjuvant CRT in patients with locally advanced rectal cancer (12) (10).…”
mentioning
confidence: 99%